2016
DOI: 10.1111/febs.13946
|View full text |Cite
|
Sign up to set email alerts
|

Lost in translation: applying 2D intercellular communication via tunneling nanotubes in cell culture to physiologically relevant 3D microenvironments

Abstract: Tunneling nanotubes (TNTs) are membranous conduits for direct cell-to-cell communication. Until the past decade, little had been known about their composite structure, function, and mechanisms of action in both normal physiologic conditions as well as in disease states. Now TNTs are attracting increasing interest for their key role(s) in the pathogenesis of disease, including neurodegenerative disorders, inflammatory and infectious diseases, and cancer. The field of TNT biology is still in its infancy, but inr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…We next asked how macrophage cytoplasm is delivered to tumor cells. There are at least two mechanisms of cytoplasmic transfer – transfer of molecules extracellularly via secretion of extracellular vesicles (EVs), and transfer of molecules through cell-to-cell contact (Lou et al, 2017; McCoy-Simandle et al, 2016; Weidle et al, 2017)). The migration-promoting cytoplasmic transfer between tumor cells described by Zomer et al was via systemic transfer of EVs, however given the close and sustained physical interactions between macrophages and tumor cells observed in our zebrafish studies, we hypothesized that the cytoplasmic transfer from macrophages to tumor cells is cell-contact mediated.…”
Section: Resultsmentioning
confidence: 99%
“…We next asked how macrophage cytoplasm is delivered to tumor cells. There are at least two mechanisms of cytoplasmic transfer – transfer of molecules extracellularly via secretion of extracellular vesicles (EVs), and transfer of molecules through cell-to-cell contact (Lou et al, 2017; McCoy-Simandle et al, 2016; Weidle et al, 2017)). The migration-promoting cytoplasmic transfer between tumor cells described by Zomer et al was via systemic transfer of EVs, however given the close and sustained physical interactions between macrophages and tumor cells observed in our zebrafish studies, we hypothesized that the cytoplasmic transfer from macrophages to tumor cells is cell-contact mediated.…”
Section: Resultsmentioning
confidence: 99%
“…TNTs have been previously reported to mediate specific direct cellcell contact between macrophages (Hanna et al, 2017;Hase et al, 2009) as well as between tumor cells (Ady et al, 2014;Lou et al, 2012Lou et al, , 2017bOsswald et al, 2015). Given the important role of macrophages in breast cancer progression and the existence of TNTs in both contexts, we investigated whether heterotypic TNTs form between macrophages and tumor cells.…”
Section: Formation Of Heterotypic Tnts Between Tumor Cells and Macropmentioning
confidence: 99%
“…The monolayer cells under 2D culture condition completely differ from in vivo status where cells grow in three dimensions (3D), in terms of cell morphology, cell-to-cell interactions, growth behavior, and interactions with extracellular matrix 30 . It has been well demonstrated that 2D cell monolayer is unable to represent the physiology of in vivo 3D tissues or organs, due to the substantially different microenvironment (e.g., mechanical and biochemical properties) in tissue architecture [36][37][38][39][40][41] .…”
mentioning
confidence: 99%